The Lactate/Pyruvate Ratio of Metabolic Modulation using Glucose Insulin Kalium and Lactate Solution and their Effect on Functional Mechanical Recovery of the Isolated Perfused Heart - Suranadi, I Wayan; Bakta, Made; Arhya, I Nyoman; Leverve, Xavier (Udayana University, 2009)
Metabolic modulation with Glucose Insulin Kalium (GIK) solution has beenreally well known in their capacity to improve post ischemic heart function. In this regardGIK intervention on post operative Coronary Artery Bypass Graft (CABG) can improveheart function recovery on reperfusion period (Goldhaber dan Weiss, 1992; Atwell et al.,1997). Post operative CABG intervention with GIK will produce a beneficial effect onthe elevation of heart energy to prevent ionic homeostasis disturbance and reactiveoxygen species (ROS) production that become the basis of reperfusion injury (Silvermandan Stern, 1994; Cross et al., 1995; Taegtmeyer et al., 1997; Opie, 1999; Lazar, 2002;Doenst et al., 2003; Trence et al., 2003).Many efforts have been made to clarify how exactly GIK works to improve postischemic heart function as in CABG. This is crucially done in order to be able to modifythe solution concerned. Although this solution has been clearly proved to improve postischemic heart function, it is not totally free from its adverse effect. Its main side effect isthat it can provoke hyperglycemic state, which contrasts with the tight glucose control incontinuously normal range for the patients who are critically ill.In this study lactate and pyruvate level in the coronary effluent were measuredfrom the isolated heart directly perfused with GIK and lactate. It was shown that thepreischemic lactate level was low and then clearly elevated as soon as the reperfusiontook place due to anaerobic metabolism. In accordance with reperfusion time lactate leveldecreased gradually. In relation with pyruvate level, this substrate evolution looked likethe appearance of lactate but its value was lower if compared with lactate.The recovery in functional mechanical activity of the post ischemic heart seems tobe much more related to the pattern of the evolution of logarithmic lactate/pyruvate ratio(L/P ratio). Logarithmic value of L/P ratio in GIK group increased since the earlyreperfusion period (+40%, p < 0.05), followed by improvement in recovery ofmechanical activity in this group which was significantly higher if compared with thecontrol group. Similar fashion was found in lactate group in regard to the evolution of thelogarithmic value of L/P ratio in this group, where its value was significantly highercompared with the control group. The logarithmic evolution pattern on L/P ratio for thisgroup increased along the reperfusion time (+34% p < 0.05).From the present study, it can be concluded that the recovery of functionalmechanical activity of the post ischemic heart perfused with GIK is through modificationon cellular lactate metabolism.